Trends in the Transformation of Modern Law under the Influence of a New Stage of Scientific and Technological Progress - I. A. Umnova-Koniukhova (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2021)
The article examines the trends of transformation of modern law under the influence of a technological breakthrough as a new stage of scientific and technological progress. The general trends of globalization and differentiation of law are highlighted, and the consequences of these trends, expressed in the growth of the number of complex branches of law that combine public and private interests, are considered. For the purpose of systematization, three main forms of globalization in law are identified: universalization, internationalization and integration. The analysis of the evolution of the legal system in the historical dimension allows to distinguish three stages of differentiation of modern law. At the first stage of the differentiation of law in the XX century, it was mainly expressed in the fragmentation of traditional branches of law. The second stage of the differentiation of law at the turn of the XX and XXI centuries is characterized by the intensive formation of complex mixed branches of law that join the institutions of public and private law for certain purposes of legal regulation. At the third, modern stage at the junction of the first and second decades of the XXI century. under the influence of scientific and technological progress, there is not only a further diversification and integration of traditional  and  new  complex  branches of law, but also a group of functional and instrumental branches of law. Th se branches of auxiliary law (due to its functional significance) determine the socio-legal technologies of regulation, implementation and development of law (for example, collision law, mediation law, digital law).The author puts forward the concept and reveals the system of branches of law of the new generation as the highest form of evolution of complex branches of law, justifies their special nature and significance in the system of law. The author also systematizes the branches of law of the new generation, taking into account the degree of their development in legal doctrine and law practice.Special attention is paid to digital law and bio-law, which most clearly indicate the impact of scientific and technological progress on law, as well as exposing the problem of the need for closer interaction of the principles and norms of law and ethics.